A New Approach to Estimating State Dependence in Consumers' Brand Choices Applied to 762 Pharmaceutical Markets. (11th July 2021) - Granlund, David
Abstract : This article shows how state dependence effects can be estimated for many markets and with few assumptions by using data on how the shares of consumers buying specific products differ between those who bought the same product on their latest purchase occasion and those who did not. Using information regarding which product was cheapest when consumers made their last purchases as instrument, I estimate that state dependence increases the probability that consumers will buy the product they bought the last time by eight percentage points. This effect is larger for women and the elderly than for men and younger consumers.